Simulador ecográfico: utilidad como herramienta de formación para la infiltración de toxina botulínica ecoguiada - Nieto Blasco, Javier (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
To perform an echograph guided infiltration is necessary previous training and experience. Based on e-learning and application of new technological environments in medical training, our goal has been to develop a learning platform for virtual medical training, through an echograph simulator. Our application works in Microsoft Windows and Macintosh. For its development multi-platform technologies have been used such as programming software Visual C++, Qt and XML code. The design of program was organized in three parts: access, visualization and mathematical functions. Our technological medical training tool allows get knowledge and practical skills for echo-guided infiltration, through a dynamic and interactive virtual environment, allowing echograph explorations without the “existence” of a real patient.
Keywords: Botulinum toxin; simulation; e-learning; echography; medical training